Understanding EFL Students’ Use of English Podcasts for Listening Skill Development - Tarisa Sepdiana; Zainuddin Zainuddin; Nina Agus Hariati (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study investigates how EFL students use English podcasts and their perceptions of the impact of using podcasts in developing their listening skills. By using a qualitative descriptive approach, data were collected through semi-structured interviews, observations, and documentation with five students of the English Education Department at Zainul Hasan Genggong Islamic university, Probolinggo. The findings reveal that students used English podcasts as a flexible learning medium to practice listening anytime and anywhere. Students engaged in several listening activities, such as replaying the audio, focusing on difficult parts, and selecting podcast topics based on their interests. Students viewed English podcasts as an effective learning medium to support listening practice, increase motivation, and help them become more familiar with spoken English. The benefits of using English podcasts include improving listening comprehension, increasing learning motivation, providing opportunities for repeated listening practice, and helping students become more accustomed to authentic English pronunciation and expressions. Thus, it can be concluded that English podcasts serve as an effective medium to support the development of EFL students’ listening skills through exposure to authentic spoken English. Keywords: EFL students, English Podcasts, Listening skills